Microbial study of household hygiene conditions and associated Listeria monocytogenes infection risks for Peruvian women. Issue 7 (22nd May 2019) - Canales, Robert A.; Wilson, Amanda M.; Sinclair, Ryan G.; Soto‐Beltran, Marcela; Pearce‐Walker, Jennifer; Molina, Margarita; Penny, Mary; Reynolds, Kelly A.
Abstract: Objectives: To develop an exposure and risk assessment model to estimate listeriosis infection risks for Peruvian women. Methods: A simulation model was developed utilising Listeria monocytogenes concentrations on kitchen and latrine surfaces in Peruvian homes, hand trace data from Peruvian women and behavioural data from literature. Scenarios involving varying proportions of uncontaminated, or 'clean', surfaces and non‐porous surfaces were simulated. Infection risks were estimated for 4, 6 and 8 h of behaviours and interactions with surfaces. Results: Although infection risks were estimated across scenarios for various time points (e.g. 4, 6, 8 h), overall mean estimated infection risks for all scenarios were ≥ 0.31. Infection risks increased as the proportions of clean surfaces decreased. Hand‐to‐general surface contacts accounted for the most cumulative change in L. monocytogenes concentration on hands. Conclusions: In addition to gaining insights on how human behaviours affect exposure and infection risk, this model addressed uncertainties regarding the influence of household surface contamination levels. Understanding the influence of surface contamination in preventing pathogen transmission in households could help to develop intervention strategies to reduce L. monocytogenes infection and associated health risks. Abstract : Objectifs: Développer un modèle d'exposition et d'évaluation des risques pour estimer les risques d'infection par la listériose chez les femmes péruviennes. Méthodes: Un modèle de simulation a été développé en utilisant des concentrations de Listeria monocytogenes sur la surface des cuisines et des latrines dans des foyers péruviens, des données de traces de mains de femmes péruviennes et des données comportementales de la littérature. Des scénarios impliquant différentes proportions de surfaces non contaminées ou «propres» et de surfaces non poreuses ont été simulés. Les risques d'infection ont été estimés pour 4, 6 et 8 heures de comportements et d'interactions avec les surfaces. Résultats: Bien que les risques d'infection aient été estimés pour tous les scénarios à différents moments (par ex. à 4, 6 ou 8 heures), les risques d'infection globaux moyens estimés pour tous les scénarios étaient ≥ 0, 31. Les risques d'infection augmentaient à mesure que les proportions de surfaces propres diminuaient. Les contacts entre la main et les surfaces générales contribuent pour le plus de changement cumulatif de la concentration de L. monocytogenes sur les mains. Conclusions: En plus de comprendre comment les comportements humains affectent l'exposition et le risque d'infection, ce modèle a traité des incertitudes quant à l'influence des niveaux de contamination des surfaces ménagers. Comprendre l'influence de la contamination de surface dans la prévention de la transmission d'agents pathogènes dans les ménages pourrait aider à développer des stratégies d'intervention pour réduire l'infection à L. monocytogenes et les risques associés pour la santé.